Ukrainian literature in the twentieth century : a reader's guide - Luckyj, George S. N., 1919-2001 (Heritage., 1992)
George S.N. Luckyj provides a survey of the main literary trends of Ukraine, its chief authors, and their works, as seem against the historical background of the present century. Luckyj provides information about literary developments both in Ukraine and in the Ukrainian emigration and diaspora.